FRI0020 Preclinical development of sarilumab, the first fully human monoclonal antibody (MAB) against IL-6r alpha: utilization and value of double humanized animal model. (23rd January 2014) - Wang, L.-H.; Xue, Y.; Liu, X.; Luo, F.; Kelly, L.; Huang, T.; Valenzuela, D.; Papdopoulos, N.; Graham, N.; Murphy, A.
Abstract : Background: Interleukin-6 (IL-6) is a mediator of inflammation. Preclinical study of human IL biology in mouse models is limited by species-restricted signaling reactivity. Genetically modified mice are used with targeted human gene replacements to evaluate sarilumab, the first fully human mAb directed against human IL-6Rα. Objectives: To evaluate sarilumab potency by testing the mAb in a mouse model of sterile inflammation where genes encoding mouse IL-6 and IL-6Rα were replaced with orthologous human genes. Methods: Sarilumab was developed using VelocImmune ® mice immunized with human IL-6R. These mice are genetically engineered to express human antibody variable domain genes similarly to replaced mouse genes. To validate the VelocImmune derived mAb against IL-6R, genetically-engineered mice were created using VelociGene ® technology by replacing both the murine Il6 gene with 4.8 kb of human IL6 genomic sequences and the portion of the mouse Il6ra gene encoding the extracellular domain of IL-6Rα (CD126) with a 45.5 kb fragment of the human IL6Ra gene encoding the corresponding extracellular domain encoding human IL-6Rα. Mice homozygous for humanized Il6 and Il6ra ( Il6 hu/hu Il6ra hu/hu ) were subjected to pharmacodynamic testing using a turpentine-induced sterile inflammation model that elicits an IL-6-dependent acute phase response. Il6 hu/hu Il6ra hu/hu mice were administered doses of sarilumab (0.015 mg/kg to 15 mg/kg) or an isotype control mAb at 16 hrs prior to SC injection of turpentine to induce inflammation. Blood samples were collected from challenged mice 20 hrs later to analyze serum amyloid A (SAA) production and circulating IL-6 levels. Results: Il6 hu/hu Il6ra hu/hu mice development and validation were based on experiments that showed: 1) functional production of human IL-6, 2) lack of responsiveness of human IL-6Rα to murine IL-6, 3) expression of human IL-6Rα on primary cells from Il6 hu/hu Il6ra hu/hu mice, 4) restoration of IL-6 signaling ability in doubly humanized mice. In the inflammation model, pre-dosing of sarilumab prevents induction of SAA production in a dose-dependent manner with an IC50 value of 1-2 mg/kg. A 70% reduction of SAA was seen at 1.5 mg/kg, a 97.5% reduction at 5 mg/kg, and at 15 mg/kg, SAA was reduced to normal levels. Concomitantly, circulating hIL-6 levels were modestly increased by turpentine challenge but elevated to a much greater extent by sarilumab at doses ≥1.5 mg/kg, consistent with either a reduction of receptor mediated clearance or feedback upregulation of IL-6 production. Conclusions: These results show that sarilumab was biologically active in a humanized mouse model of acute inflammation and achieved a dose-dependent reduction in SAA following turpentine injection, with an IC50 value of 1-2 mg/kg, with normalization of the acute phase response evident at doses ≥5 mg/kg. Creation of genetically engineered mice with human gene replacements provides a series of tools to produce fully human mAbs and evaluate the efficacy of antibody candidates that have limited cross-species reactivity under in vivo conditions. Acknowledgements: VelocImmune ® and VelociGene ® are registered trademarks of Regeneron. Disclosure of Interest: L.-H. Wang Shareholder of: Regeneron, Employee of: Regeneron, Y. Xue Employee of: Regeneron, X. Liu Shareholder of: Regeneron, Employee of: Regeneron, F. Luo Employee of: Regeneron, L. Kelly Shareholder of: Regeneron, Employee of: Regeneron, T. Huang Shareholder of: Regeneron, Employee of: Regeneron, D. Valenzuela Shareholder of: Regeneron, Employee of: Regeneron, N. Papdopoulos Employee of: Regeneron, N. Graham Employee of: Regeneron, A. Murphy Shareholder of: Regeneron, Employee of: Regeneron